Adolescent brain cognitive development neurocognitive prediction : first Challenge, ABCD-NP 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13, 2019, Proceedings /: first Challenge, ABCD-NP 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 13, 2019, Proceedings. (2019) - Unknown
No abstract available